2005
DOI: 10.1373/clinchem.2005.051557
|View full text |Cite
|
Sign up to set email alerts
|

Simple Cystatin C–Based Prediction Equations for Glomerular Filtration Rate Compared with the Modification of Diet in Renal Disease Prediction Equation for Adults and the Schwartz and the Counahan–Barratt Prediction Equations for Children

Abstract: Background: Serum creatinine is the most commonly used marker for estimation of glomerular filtration rate (GFR). To compensate for its drawbacks as a GFR marker, several prediction equations including several parameters are being used, with the Modification of Diet in Renal Disease (MDRD), Schwartz, and CounahanBarratt equations being the ones most widely accepted for estimation of relative GFR in mL ⅐ min ؊1 ⅐ (1.73 m 2 ) ؊1 . The present study analyzes whether these GFR prediction equations for adults and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
302
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(318 citation statements)
references
References 39 publications
6
302
0
10
Order By: Relevance
“…In contrast to the MDRD equation, which was calculated from a large population in a multicenter study, CysC-based equations were created and validated in smaller samples using different gold standard measurements for GFR. Table 3 highlights some CysCbased equations for adults (29,45,(51)(52)(53)(54)(55)(56).…”
Section: Equations Estimating Gfr Based On Cystatin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the MDRD equation, which was calculated from a large population in a multicenter study, CysC-based equations were created and validated in smaller samples using different gold standard measurements for GFR. Table 3 highlights some CysCbased equations for adults (29,45,(51)(52)(53)(54)(55)(56).…”
Section: Equations Estimating Gfr Based On Cystatin Cmentioning
confidence: 99%
“…The vast majority, when comparing bias, precision, accuracy, and correlation, found CysC-based equations to be superior to creatinine-based equations as estimates of GFR (45,52,53), while some reported no difference in the performance of CysC-and creatinine-based equations (29,54). Recently, in order to improve the estimated kidney function, estimated GFR equations were developed, which incorporate both SCr and CysC.…”
Section: Equations Estimating Gfr Based On Cystatin Cmentioning
confidence: 99%
“…Serum cystatin C is a relatively new endogenous marker that offers the advantage of a constant production by all nucleated body cells and its almost entire catabolism at the proximal tubule (1). In clinical studies, serum cystatin C has been found to be a good marker for predicting GFR (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the formulas involving cystatin C presented better 20,47,48 or similar 27,49 performances in relation to the equations with creatinine, according to researchers. For some, the combination of serum creatinine and cystatin C in formulas is the best option when considering demographic data.…”
Section: Cystatin Cmentioning
confidence: 96%
“…Against the expectation of being a proper marker, in this group, formulas based on cystatin C overestimate GFR in individuals with higher body mass index (BMI). 46 It is important to emphasize that some formulas have been developed in the past few years with the objective to better evaluate renal function with cystatin C, just as with serum creatinine, to estimate GFR, 20,22,27,[47][48][49][50][51] as demonstrated in Table 2.…”
Section: Cystatin Cmentioning
confidence: 99%